FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PRAKTIK IBU DALAM PERSONAL HYGIENE ANAK RETARDASI MENTAL DI SEKOLAH DASAR LUAR BIASA (SDLB) NEGERI SEMARANG - Raisasari, Irma Ivonita; Cahyo, Kusyogo; Riyanti, Emmy (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Mentally retarded children are late on all aspects of growth and have limitations in their physical or mental abilities. They have difficulties in their personal hygiene and have to rely on other people, ecspecially their parents. Semarang City has the most disabled children in Central Java. There are 1,414 disabled children and 968 mentally retarded children in Semarang. The goal of this research is to analyze factors that correlates with a mothers practices in the personal hygiene of mentally retarded children in Sekolah Dasar Luar Biasa (SDLB) Negeri Semarang.This is a descriptive analytic research with quantitative method using Cross Sectional approach. The samples of this research were 65 mothers of mentally retarded children in Sekolah Dasar Luar Biasa (SDLB) Negeri Semarang. Chi Square is used to analyze the data.The practice of respondents in maintaining personal hygiene of mentally retarded children is good, that is equal to 58,5%. Respondents aged 29-41 years have a percentage of 50.8%, most respondents have low education level (doesn’t go to school – graduates from SMP) that is 64.6%, respondents mostly as housewives is 83.1%. Knowledge of respondents about personal hygiene is good that is equal to 61,5%, respondent attitude mostly good that is 66,2%. Source of information about personal hygiene obtained by respondent mostly good that is 73,8%, parenting of respondent is 50,2% is good, support of husband of part of respondent is support that is 78,5% and support teacher that support that is amount 66,2 %.This research shows that knowledge (p=0,029), attitude (p=0,001) and information source (p=0,049) correlates with a mothers practices in the personal hygiene of mentally retarded children while age (p=1,000), education (p=0,280), job (p=0,178), child upbringing (p=0,690), husband's support (p=0,100) and support from teacher (p=0,074) doesn't.